Appendix perforation: contributing risk factors - Pal, Gopal Chandra; Badhan, Raisa Enayet; Chowdhury, M. Tanuwar Islam; Moushumi, Rubaiya Sharmeen (International Surgery Journal, 2025)
Background: Acute appendicitis is the most common abdominal surgical emergency. When it progresses to perforation, it leads to prolonged recovery and increased mortality. This study aims to identify risk factors for appendiceal perforation in the local population. Methods: A hospital-based study was conducted at Faridpur Medical College Hospital from June 2014 to June 2015 on 200 patients diagnosed with appendicitis. Data were collected using structured forms and analyzed statistically. Results: The majority of patients were aged 15-25 years (32.5%) and 26-35 years (28.5%). Perforation was more common at extreme ages. Low education levels (41.89% illiterate, 36.48% primary education) and poor socioeconomic status (42%) were significant risk factors. Among 200 cases, 74 (37%) had perforated appendicitis, while 126 (63%) had inflamed appendicitis. Delay in hospitalization increased the risk, with only 5.4% of perforated cases presenting on the first day. Common symptoms included abdominal pain (100%), nausea/vomiting (73.5%), fever (61%) and anorexia (64.5%). Right lower quadrant tenderness was present in all cases, while rebound tenderness and fever occurred in 94%. Leukocytosis (>10×10⁹/L) was observed in over half of the patients. Obstruction due to fecolith (72.5%) was the leading cause of perforation. Conclusions: Appendiceal perforation is associated with delayed diagnosis, low socioeconomic status and obstruction. Timely intervention, better health awareness and risk factor prevention can reduce complications and improve patient outcomes. Proper clinical evaluation remains crucial for effective management.